Description and ontogenetic morphometrics of eggs and instars of Triatoma costalimai Verano & Galvão, 1959 (Hemiptera: Reduviidae: Triatominae) - Raigorodschi, Raquel S; Rocha, Dayse S; Jurberg, José; Galvão, Cleber (Zootaxa, 2011)
The triatomines are characterized by obligate hematophagy throughout their life cycle, and they are responsible for the transmission of T. cruzi, the etiological agent of Chagas disease, to humans and other mammals. Triatoma costalimai was described by Verano & Galvão (1959) based on nine specimens found among rocks in the municipality of Taguatinga, Goiás State, Brazil. The species was named in honor of Ângelo Moreira da Costa Lima, an entomologist from the Oswaldo Cruz Institute. It is a sylvatic species but has been found in peridomestic areas and human dwellings in the States of Bahia, Goiás, Mato Grosso, and Minas Gerais, Brazil. Nymphs and eggs of T. costalimai were described using optical microscopy. The eggs are ellipsoid in shape, and most cells are pentagonal. Nymphs display morphological differences, and the colors, legs, and head maintain the same pattern in most instars. Ontogenetic morphometrics was used to visualize the changes that occur during nymphal development. The results showed the discrimination of all instars, but the largest change occurs between the first and second instars.